A decade of agricultural research: bibliometric analysis of Malaysian publications (2015-2024) - Sahak, Mohd Dasuki; Hasan, Nur Azleen; Sa’ari, Haziah (2024)
This study presents a comprehensive bibliometric analysis of Malaysia’s agricultural-related publications from the Scopus database, covering the years 2015 to 2024 and encompassing 29,086 documents. The analysis employed Scopus Analyze Search Results and Bibliometrix, an RStudio package, to ensure robust data analysis. 'Country affiliation' and 'Subject filters' were utilised to accurately represent Malaysia’s Agricultural and Biological Sciences publications, acknowledging the related nature of these fields in the Scopus database. The study identifies publication types and examines annual scientific production, authorship patterns, citation metrics, subjects, topics, and the social structures of countries and institutions. The findings indicate a consistent annual growth in Malaysian agricultural research, which aligns with the Malaysia Plan initiative to enhance higher education and research institutions. Universiti Putra Malaysia (UPM) leads with 7,635 publications, followed by Universiti Kebangsaan Malaysia (3,065), Universiti Malaya (2,875), Universiti Sains Malaysia (2,752), and Universiti Malaysia Terengganu (2,289). Notably, two articles surpassed 1,000 citations: “Anthocyanidins and Anthocyanins: Colored Pigments as Food, Pharmaceutical Ingredients, and Their Potential Health Benefits” by Khoo et al. (2017) and “Overviews of Biological Importance of Quercetin: A Bioactive Flavonoid” by Anand David et al. (2016). This study underscores the significance of bibliometrics in evaluating research and publication activities, showcasing the proficiency of librarians in conducting bibliometric analyses using large datasets and RStudio. The findings of this study are significant to the field of agricultural and biological sciences, providing valuable insights into the trends and developments in Malaysian agricultural research.